Differentiation Between G1 and G2/G3 Phyllodes Tumors of Breast Using Mammography and Mammographic Texture Analysis - Cui, Wen Jing; Wang, Cheng; Jia, Ling; Ren, Shuai; Duan, Shao Feng; Cui, Can; Chen, Xiao; Wang, Zhong Qiu (Frontiers in Oncology, 2019)
Purpose To determined the potential of mammography (MG) and mammographic texture analysis in differentiation between Grade 1 (G1) and Grade 2/ Grade 3 (G2/G3) phyllodes tumors (PTs) of breast. Materials and methods A total of 80 female patients with histologically proven PTs were included in this study. 45 subjects who underwent pretreatment MG from 2010 to 2017 were retrospectively analyzed, including 14 PTs G1 and 31 PTs G2/G3. Tumor size, shape, margin, density, homogeneity, presence of fat or calcifications, halo-sign as well as some indirect manifestations were evaluated. Texture analysis features were performed using commercial software. Receiver operating characteristic curve (ROC) was used to determine the sensitivity and specificity of prediction. Results G2/G3 PTs showed larger size (> 4.0 cm) compared with PTs G1 (64.52% vs. 28.57%, p = 0.025). Strong lobulation or multinodular confluent was more common in G2/G3 PTs compared to PTs G1 (64.52% vs. 14.29%, p = 0.004) . Significant differences were also observed in tumours’ growth speed and clinical manifestations (p = 0.007, 0.022, respectively) . 10 texture features showed significant differences between the two groups (p＜0.05) , Correlation_AllDirection_offset7_SD and ClusterProminence_AllDirection_offset7_SD were independent risk factors. The area under the curve (AUC) of imaging-based diagnosis, texture-based diagnosis and the combination of the two approaches were 0.805, 0.730 and 0.843 (90.3% sensitivity and 85.7% specificity) . Conclusions Texture analysis has great potential to improve the diagnostic efficacy of MG in differentiating PTs G1 from PTs G2/G3.